The implementation of the task-based language learning approach ─ a strategy to enhance second year students' vocabulary deficiency at Centro Escolar Mercedes Monterrosa de Cárcamo during 2020 - Bolaños Peraza, Yandy Abigail; Castro Martínez, Cristian Israel; Fuentes Medina, Alvin Harol; González Galeano, Yensy Marilin (2024)
The researchers developed the investigation “The Implementation of the Task-Based Language Learning Approach ─ A Strategy to Enhance Second Year Students' Vocabulary Deficiency at Centro Escolar Mercedes Monterrosa de Cárcamo During 2020” in order to verify if implementing a lesson plan based on the Task-Based Language Learning (TBLL) model can help second year students’ management of a proper level of vocabulary. Therefore, this study proposes teachers a different class structure and environment where students can acquire new vocabulary in an easy and enjoyable way